How Effective is Experiental Learning in Entrepreneurship Education? A Review of The Concept and Its Application - Ismanto, Deny; Rini, Poppy Laksita; Jatmiko, Bambang; Gumelar, Bagus; Rahmi, Mustika; Solihudin, Ahmad Rizal (Journal of Vocational Education Studies, 2025)
The challenge of effectively teaching entrepreneurship and fostering students' entrepreneurial skills and business initiation has drawn significant attention. As the solution for this issue, experiential learning system (ELS), a pedagogical strategy in which students learn by doing, becomes more prevalent technique of teaching entrepreneurship. Therefore, this research uses the literature review method to analyze the effectiveness of using ELS in implementing entrepreneurship development programs. This research was carried out by collecting relevant literature sources, analyzing the content of the literature, and compiling the findings in the literature into a comprehensive understanding framework. The systematic literature review approach used in this study can provide identification and construct what further research needs to be done in the future including determining the characteristics of the variables that influence the phenomenon being studied. In conclusion, The findings demonstrate that experiential learning positively impacts the development of entrepreneurial competencies and skills. Nevertheless, while various experiential activities offer distinct advantages for entrepreneurship education, they also pose challenges that need to be addressed. Thus, the recommendations given through this paper are the implementation of Experiential Learning in Entrepreneurship Education could be developed with the interdisciplinary integration (engineering, health, art, and science) practice, implement the usage of technology and AI, and drive the business mission into social entrepreneurship.